“Lottery Equivalents”: Reduction of the Certainty Effect Problem in Utility Assessment - McCord, Mark; de Neufville, Richard (Management Science, 1986)
This note describes a simple procedure for assessing utility functions which avoids many difficulties of the standard techniques. The conventional methods suffer from at least three drawbacks; they (1) generate utility functions that depend on the probability levels used; (2) chain responses from one question to the next, so that any bias is propagated and even magnified; and (3) change ranges and reference points constantly, introducing range effects and other distortions. Noting the evidence linking the dependence of utility functions on the “certainty effect,” our method: (1) compares lotteries with other lotteries rather than certain amounts; (2) does not “chain” responses; and (3) consistently uses “elementary lotteries” which control for range and reference points. Experimental work supports the proposed procedure.